2011
DOI: 10.1108/13522751111099337
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of men's brand relationships

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…These homosexual informants' fear of being perceived as feminine by others because of the brands they purchase echoes prior findings with heterosexual men of Tuncay-Zayer and Neier (2011), with regard to men's relationships with grooming brands. We reveal here that, in both cases, this behavior is connected with a discourse about "resistant masculinity" or "instrumental masculinity" from our respondents.…”
Section: Brands As Gender Threatssupporting
confidence: 73%
See 2 more Smart Citations
“…These homosexual informants' fear of being perceived as feminine by others because of the brands they purchase echoes prior findings with heterosexual men of Tuncay-Zayer and Neier (2011), with regard to men's relationships with grooming brands. We reveal here that, in both cases, this behavior is connected with a discourse about "resistant masculinity" or "instrumental masculinity" from our respondents.…”
Section: Brands As Gender Threatssupporting
confidence: 73%
“…Some researchers have suggested that today's masculinities are characterized more by ambiguity and malleability than by the hyper-masculine perspective (Littlefield, 2010). Hence, some contemporary masculinities are oriented toward more gender-egalitarian ideals, such as the "metrosexuals" (Tuncay, 2006;Tuncay-Zayer and Neier, 2011) or the "at-home fathers" who nevertheless use capitalizing practices to improve the status of domestic activities traditionally coded as feminine (Coskuner-Balli and Thompson, 2013). More recently, Klasson and Ulver (2015) showed that in Sweden, a country permeated by the ideology of gender equality, masculinities are more complex, diverse and hybrid than the lone perspective of hegemonic masculinity.…”
Section: Masculinities and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this spirit, the four answers to each of the four questions in Table 1 paint word pictures. 4. Combine the answers (but not the questions) into small vignettes, each vignette comprising a minimum of two answers, and a maximum of four answers.…”
Section: D4mentioning
confidence: 99%
“…That is, the chemistry of cosmetics, the formulation, and the possible toxicological aspects are part of the science of cosmetics, but the mind of the cosmetic customer is not. Of course there are general studies, but really very few of a specific nature to which a marketer can go to understand that customer mind [1][2][3][4] How does one communicate science and beauty in a simple way, especially when the science involves new technology (e.g. fullerenes with nano-properties appropriate for and valuable to cosmetic products; [5,6].…”
Section: Introductionmentioning
confidence: 99%